2021
DOI: 10.1038/s42003-021-02910-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards organoid culture without Matrigel

Abstract: Organoids—cellular aggregates derived from stem or progenitor cells that recapitulate organ function in miniature—are of growing interest in developmental biology and medicine. Organoids have been developed for organs and tissues such as the liver, gut, brain, and pancreas; they are used as organ surrogates to study a wide range of questions in basic and developmental biology, genetic disorders, and therapies. However, many organoids reported to date have been cultured in Matrigel, which is prepared from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
165
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(206 citation statements)
references
References 225 publications
1
165
0
Order By: Relevance
“…Moreover, PDM are cultured in suspension, whereas PDO are usually cultured in ECM matrix from mouse tumors (Matrigel). Influences of animal origin and batch-dependent differences in the composition of matrigel on comparability with human tumor tissue need to be considered for PDO [ 64 , 65 ]. In contrast, PDM are cultured in defined medium without the addition of animal components.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PDM are cultured in suspension, whereas PDO are usually cultured in ECM matrix from mouse tumors (Matrigel). Influences of animal origin and batch-dependent differences in the composition of matrigel on comparability with human tumor tissue need to be considered for PDO [ 64 , 65 ]. In contrast, PDM are cultured in defined medium without the addition of animal components.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the mechanical properties of synthetic hydrogels simply require modification of monomer to crosslinker ratio or polymer contents independent of ligand density for cell adhesion [ 257 , 258 , 259 ]. Natural hydrogels often contain great batch-to-batch variability and ill-defined protein composition [ 243 , 260 ], making reproducibility and consistency challenging [ 243 , 261 , 262 ]. For PEG or PAAm synthetic hydrogels, the polymer content, mesh size, and elastic modulus can be chemically predetermined and synthesized with trivial variation between batches [ 259 , 263 ].…”
Section: Preclinical Models For Trafficking and Infiltrationmentioning
confidence: 99%
“…Sequencing studies demonstrated preserved mutational patterns among organoids when compared to the primary tumor sample, indicating organoids may make excellent patient specific models for personalized drug susceptibility testing ( 50 ). It should be noted that Matrigel is frequently used for organoid culture but is a poorly characterized medium derived from mouse sarcoma cells and may alter normal cellular function ( 57 ). New methods are being developed to grow organoids without Matrigel ( 57 ).…”
Section: Organoid Modelsmentioning
confidence: 99%
“…It should be noted that Matrigel is frequently used for organoid culture but is a poorly characterized medium derived from mouse sarcoma cells and may alter normal cellular function ( 57 ). New methods are being developed to grow organoids without Matrigel ( 57 ).…”
Section: Organoid Modelsmentioning
confidence: 99%